Sensing properties of femtosecond laser-inscribed long period gratings in photonic crystal fiber - Kalli, Kyriacos; Allsop, Thomas P.; Zhou, Kaiming; Smith, Graham N. (My University, 2011)
The use of near infrared, high intensity femtosecond laser pulses for the inscription of long period fiber gratings in photonic crystal fiber is reported. The formation of grating structures in photonic crystal fiber is complicated by the fiber structure that allows wave-guidance but that impairs and scatters the femtosecond inscription beam. The effects of symmetric and asymmetric femtosecond laser inscriptions are compared and the polarization characteristics of long period gratings and their responses to external perturbations are reported.
Keywords: Photonic crystals; Femtosecond lasers; Fibers; Open access publishing